THE STRUGGLE OF HOMOSEXUAL AGAINST DISCRIMINATION IN THE MAIN CHARACTER of MILK MOVIE - MASLIVEFA, MAHARANI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Maslivefa, Maharani.  2008.,  The Struggle of Homosexual  Against Discrimination in the Main Character of Milk Movie. Study Program of English, University of Brawijaya.Supervisor: (1) M. Andhy Nurmansyah M. Hum. ; Co-supervisor: Winda Candra  Hantari M.A.Keywords: discrimination, homosexual, struggleMilk  is one of American biographical films which has a relationship with the history of America that points out the discrimination of homosexual in that era. In the 1970’s era there are lots of movements include gender movement like feminist and gay or lesbian group. History also shows that homosexuals have been discriminated. Homosexuals often assumed as a product of sick environment because of their sexual deviance, that is why they get discriminations from society. Bad stereotype from society makes homosexuals have a limitation of occupation also in politics. Because of this problem Harvey as a homosexual decided to struggle the rights for homosexuals. Queer approach which stressed on gender discrimination is applied in this study. This  theory describes about critics of  the relation between  representations of  same  sex, political power  of sexuality and social. Queer theory has been claimed and proved that it is the field in which analysts might productively explore that politics and people are identified in terms of sexualities.  The result of the research shows that through politics Harvey can fight for the rights of homosexuals especially in the society, and as a politician. Gay and lesbian political movement are stressed to ethnic politics and race minorities. As a homosexual he can be considered as one who supports the movement for homosexual because as a supervisor which struggle hard for the rights especially in San Francisco. For further researches, it is recommended to use historical approach. Since Milk which set in the 1970’s era that there are many movements appears includes gender movement that can be explained historically.